THE EFFECT OF CANOLA MEAL APPLICATION IN THE DIET OF DAIRY COWS OF HOLSTEIN BREED IN BAYSERKE AGRO LLP - A.A. Spanov,; D.M. Bekenov,; D.T. Sultanbai,; G.K.Zhaksylykova,; A.D.Baimukanov, (Academic Journal of Physical and Chemical Sciences, 2019)
The impact of canola meal on dairy productivity and qualitative indicators of milk in Holstein breed cows was studied under the conditions of Bayserke Agro LLP. The prime cost of milk was calculated with the inclusion of soybean cake and canola meal as well as the average dry matter intake in the diet when the nutritional breakdown of the experimental and control groups changed in a comparative aspect.